Strategi Komunikasi Organisasi di Internal LSO HWFC dalam Menjaga Motivasi Para Kader - Rangga Dwiekie; Rizki Agus Sallam; Keysza Nurmuzaffar; Hafizh Aulia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
An organization is an association of various people who have the same goals and missions and are structured. However, the existence of different motivations between people in the organization is one of the problems for the effectiveness of communication within the organization. Hizbul Wathon Football Club, Faculty of Social and Political Sciences, University of Muhammadiyah Jakarta, in the process of sustaining the organization, intergroup communication tactics are needed to achieve organizational goals. Therefore, it makes researchers interested in conducting research with the title